PENGARUH PEMBELAJARAN JARAK JAUH DAN KOMPETENSI ABAD 21 TERHADAP KESIAPAN KERJA DI SMK PEMBANGUNAN NASIONAL PURWODADI - Shony Angga Andrian Pradana; Bayu Ariwibowo; Fahmy Fahmy; Budiyanto Budiyanto (Journal of Vocational Education and Automotive Technology, 2025)
Background of the problem The development of 21st century competencies requires someone to master various skills, including technology, information and communication skills. So it is an obligation for a teacher to provide distance learning or better known by the abbreviation PJJ. This shows that PJJ plays an important role not only in the development of 21st century competencies but also during the pandemic after COVID-19. However, from the information obtained, all students at Purwodadi National Development Vocational School have smartphones that are used in distance learning. The objectives of this research are: (1) to determine the effect of distance learning on work readiness, (2) to determine the effect of 21st century competencies on work readiness, (3) to determine the effect of distance learning and 21st century competencies on work readiness. The type of research used is quantitative research with a descriptive approach that is ex post facto in nature. Data collection techniques using documentation and questionnaires. The population and sample were 126 and 96 students. The data testing used is a validity test and a reliability test. Test data analysis requirements using normality test, linearity test, autocorrelation test, multicollinearity test, and heteroscedasticity test. Meanwhile, data hypothesis testing uses simple regression tests, multiple regression tests, T tests, F tests, R square tests (determinants) using the help of the SPSS data processing program version 24.0. The results of the analysis show (1) Distance learning on work readiness in the strongly agree category. (2) 21st century competency towards work readiness in the strongly agree category. (3) There is an influence of distance learning and 21st century competencies on work readiness. Which is proven by the results of the F test which shows a significance value (Sig) = 0.000 < 0.05 and the calculated F value = 131.046 > t table 1.41.